Anatomical proximity dictates successful ablation from adjacent sites for outflow tract ventricular arrhythmias linked to the coronary venous system. Issue 3 (10th December 2018) - Shirai, Yasuhiro; Santangeli, Pasquale; Liang, Jackson J; Garcia, Fermin C; Supple, Gregory E; Frankel, David S; Riley, Michael P; Lin, David; Schaller, Robert D; Dixit, Sanjay; Callans, David J; Zado, Erica S; et al.
Abstract: Aims: Catheter ablation of outflow tract ventricular arrhythmias (OTVAs) with the earliest activation within the coronary venous system (CVS) can be challenging. When ablation from the CVS is not feasible or ineffective, an approach from anatomically adjacent site(s) can be considered. We report the outcomes of an anatomical approach for OTVAs linked to the CVS. Methods and results: We retrospectively analysed 665 OTVA patients. Of these, 65 (9.8%) had the earliest activation within the CVS. In 53 (82%) cases, an anatomical approach was attempted. The targeted adjacent anatomical structure was the endocardial left ventricular outflow tract (LVOT) in 24 (45%), the left coronary cusp or the left/right cusp junction in 17 (32%) patients, and the right ventricular outflow tract (RVOT) in 12 (23%). The anatomical approach was successful in 26 (49%) patients (27% from the coronary cusps, 65% from the LVOT, and 8% from the RVOT). The difference in activation times between the earliest activation site within the CVS and the targeted site was not significantly different between the successful and unsuccessful groups (14.2 ± 11.2 ms vs. 13.2 ± 9.3 ms; P  = 0.89). The anatomical distance from the earliest activation site to the targeted site was shorter for the successful group (9.7 ± 2.4 mm vs. 13.1 ± 6.5 mm; P  < 0.05). In particular, when the anatomical distance was >12.8 mm, anatomical approach was successful in only 1/13 (8%). Conclusion: In patients with OTVAs linked to the CVS, an anatomical approach targeting an adjacent site can be effective, particularly when the distance between the sites is <12.8 mm.